(untitled) (Agroindustrial Science, 2026)
Accurate estimation of site quality is essential for forest planning, as it enables growth projection, prioritization of suitable areas, and optimization of management decisions. For native tropical species, the availability of site index models is still limited, which constrains the development of sustainable plantations. This study estimated the site index (SI) for Dipteryx ferrea and Simarouba amara using the Schumacher and Chapman–Richards models. A total of 48 D. ferrea trees (1 – 13 years) and 113 S. amara trees (1 – 12 years) from experimental plantations were analyzed. The Chapman–Richards model provided a better fit for D. ferrea (R² = 0.948; RMSE = 1.007), while the Schumacher model performed best for S. amara (R² = 0.949; RMSE = 1.626). Anamorphic SI curves with a base age of 10 years were developed to estimate SI and classify productive sites. Results indicate notable early growth in D. ferrea despite its high wood density, highlighting the need for further research. This study represents the first formal SI estimation for D. ferrea and provides a useful tool for the sustainable management of tropical forest plantations.